Modelling fatigue crack growth behaviour of a surface crack in rail steel - Kwok, Yan Ting (2019)
To meet the increasing societal demands and expectations, railway industries capitalise on the advent and advancement in technology and by doing so, are able to attain higher travelling speeds and increased capability to carry heavier loads. However, the increase in speeds and axle loads might compromise the integrity of the rail infrastructure; affecting rolling contact fatigue (RCF) at the contact surface between rail and wheel, traction power, stress concentrations, and progressive wear. This report aims to analyse the crack initiation and propagation mechanisms stemming from RCF in rails. In addition, this project identifies certain variables which might affect the crack initiation and propagation growth; such as varying of pressure as well as initial crack angles. Through the various stimulations conducted using Abaqus, the author hopes to deduce the correlations between the variables with regard to crack growth, especially the rate of crack growth propagation. For validation, the stimulations’ results will be compared to relevant experimental studies.